Acute effects of single dose transcranial direct current stimulation on muscle strength: A systematic review and meta-analysis - Lattari, E.; Oliveira, B. R. R.; Sobral Monteiro Júnior, R.; Rodrigues Marques Neto, S.; Oliveira, A. J.; Maranhão Neto, G. A.; Machado, S.; Budde, H. (PLOS ONE, 2018)
Previous studies investigating the effects of transcranial direct current stimulation (tDCS) on muscle strength showed no consensus. Therefore, the purpose of this article was to systematically review the literature on the effects of single dose tDCS to improve muscle strength. A systematic literature search was conducted on PubMeb, ISI Web of Science, SciELO, and Scopus using search terms regarding tDCS and muscle strength. Studies were included in accordance with Population, Intervention, Comparison, Outcomes, and Setting (PICOS) including criteria. Healthy men and women, strength training practitioners or sedentary were selected. The acute effects of single dose anode stimulus of tDCS (a-tDCS) and the placebo stimulus of tDCS (sham) or no interventions were considered as an intervention and comparators, respectively. Measures related to muscle strength were analyzed. To conduct the analyses a weighted mean difference (WMD) and the standardized mean difference (SMD) were applied as appropriate. A total of 15 studies were included in this systematic review and 14 in meta-analysis. Regarding the maximal isometric voluntary contraction (MIVC), a small effect was seen between tDCS and Sham with significant difference between the conditions (SMD = 0.29; CI95% = 0.05 to 0.54; Z = 2.36; p = 0.02). The muscular endurance measured by the seconds sustaining a percentage of MIVC demonstrated a large effect between tDCS and Sham (WMD = 43.66; CI95% = 29.76 to 57.55; Z = 6.16; p < 0.001), showing an improvement in muscular endurance after exposure to tDCS. However, muscular endurance based on total work showed a trivial effect between tDCS and Sham with no significant difference (SMD = 0.22; CI95% = -0.11 to 0.54; Z = 1.32, p = 0.19). This study suggests that the use of tDCS may promote increase in maximal voluntary contraction and muscular endurance through isometric contractions.